La predicación de san Josemaría. Descripción de una fuente documental / The Preaching of Saint Josemaría. Description of a Documentary Source - José Antonio Loarte (Studia et Documenta)
The author explains the way in which the collection of transcripts of Saint Josemaría Escrivá de Balaguer’s oral preaching, at present conserved in the General Archive of the Prelature of Opus Dei, was formed. He also describes the collection’s importance and its current situation.